Respuesta :

Given:

The expression is:

[tex]\dfrac{60m^{-2}n^6}{5m^{-4}n^{-2}}[/tex]

To find:

The equivalent expression.

Solution:

We have,

[tex]\dfrac{60m^{-2}n^6}{5m^{-4}n^{-2}}[/tex]

It can be written as:

[tex]=\dfrac{60}{5}\times \dfrac{m^{-2}}{m^{-4}}\times \dfrac{n^6}{n^{-2}}[/tex]

[tex]=12\times m^{-2-(-4)}\times n^{6-(-2)}[/tex]             [tex][\because \dfrac{a^m}{a^n}=a^{m-n}][/tex]

[tex]=12\times m^{-2+4}\times n^{6+2}[/tex]

[tex]=12m^{2}n^{8}[/tex]

Therefore, the correct option is A.